Analysis of Medicine Delays for Acute Respiratory Infections in Hospitals in the Jakarta Regional - Pujianto, Hendri; Nasihardani, Dana; Wiyatno, Tri Ngudi; Saputra, Jacky Cahaya; Satrio, Renno (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2025)
This study examines the causes of delays in providing medication to Acute Respiratory Infection (ARI) patients in hospitals within the Jakarta region and develops strategies to address this issue. The research findings, based on the Analytic Hierarchy Process (AHP) method reveal that empty stock at the distributors have the most significant impact on medication distribution delays, followed by wrong branch selection. The SWOT analysis results show that the Empty Stock at the Distributor is in quadrant III position which requires minimizing weaknesses to seize opportunities. Meanwhile, the alternative of wrong branch selection is in quadrant I which requires utilizing strengths to seize opportunities. It can be concluded that this indicates the company must utilize strengths to reduce weaknesses and seize opportunities. Strategies to enhance the efficiency of pharmaceutical distribution is using an integrated stock monitoring system and use of real-time stock monitoring system and strategically collaborating with distributors. The system helps companies manage stock more effectively, efficiently, and organized, while increasing competitiveness in the market.Collaboration with distributors become a key step to speed up the distribution process, reduce the risk of shortages or overstocks, and improve customer satisfaction through more timely and efficient deliverie. This research contributes theoretically to the integration AHP-SWOT approach focused on optimizing supply chain management can suggest strategy improving hospital procurement processes, and reducing ISPA medication distribution delays to enhance service level agreement which is necessary to enhance the quality of medical services in Jakarta.